User requirement validation: challenge exploration in pre-project execution - Muhamad Idaham, Umar Ong; M. A., Ameedeen (IOP Publishing Ltd, 2020)
The need for validation technique for user requirement or in other term Tender Specification at the Request for Tender (RFT) is vital. Without much resource for vendor to dispose of, the outcome of this research will proof useful. The purpose of this article is to determine the gap of initial and finish software product, method of eliminate or mitigate those gaps, list of OO artefacts and their relevancy towards the research. Finding of this article will be the basis of interconnecting user requirement specification and metarequirement via UML. Based on the result, RE plays an important role in the survivability of a project, there are a few researches being done for solutions in the field of RFT specification validation, UML is the most relevant artefacts and usability of UML diagram ranked based on consistency is relevant toward connecting UML and meta-requirement. It is suggested that further research is to be carried out that will define the connection between user requirement specification in the form of UML to meta-requirement in order to achieve the overall objective of the research.